If it's not what You are looking for type in the equation solver your own equation and let us solve it.
n+18=10-(-2)
We simplify the equation to the form, which is simple to understand
n+18=10-(-2)
Remove unnecessary parentheses
n+18=10+2
We move all terms containing n to the left and all other terms to the right.
+1n=+10+2-18
We simplify left and right side of the equation.
+1n=-6
We divide both sides of the equation by 1 to get n.
n=-6
| -7-3x=72 | | p(0)=3(0)+14 | | p(0)=3(0)+14 | | p(0)=3(0)+14 | | p(0)=3(0)+14 | | 9m-1=35 | | -13x+20=17x-100 | | -13x+20=17x-100 | | -7-15= | | 6x-2(x-1)=26 | | 10X*20=800 | | 3(2a+1)=8a-5 | | 4m-2m=4 | | 10x^2-60x+90=0 | | 5x+8x-51=34-4x | | 15n-5n-4n=6 | | 1*3+2(14-8)+7= | | 78+r=15 | | 15-2.45= | | -8n-(-15n)-(-16)=-5 | | 9x^2+42+49=0 | | 6(x-6)+2=8x-12 | | 4x-1=6x+6 | | 45x^3-35x^2+72x-56=0 | | -4x+-10=10 | | 21(x^2+x-2)=0 | | 9x^2+42=-49 | | 9x^2+42=-49 | | 8a+6=22 | | -7-3x=36 | | -3(3-4x)=63 | | 10x*20=60 |